ICT diffusion, foreign direct investment and inclusive growth in sub-Saharan Africa - Isaac Kwesi Ofori; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
This study examines the joint effects of ICT diffusion (composed of access, usage and skills), and foreign direct investment (FDI) on inclusive growth in sub-Saharan Africa (SSA). The study draws on data from the World Bank's World Development Indicators, and the Global Consumption and Income Project for the period 1980-2019 for the analysis. The study provides evidence robust to several specifications from ordinary least squares and dynamic system GMM estimation techniques to show that: (1) FDI and ICT diffusion and corresponding components (ICT access, usage, skills) induce inclusive growth in SSA; (2) compared to its direct effect, FDI is remarkable in fostering shared growth in SSA in the presence of greater ICT diffusion, and (3) compared to ICT access and usage, ICT skills are more effective in driving inclusive growth in SSA. Overall FDI modulates ICT dynamics to engender positive synergy effects on inclusive growth. Policy recommendations are provided in line with the implementation of the African Continental Free Trade Area (AfCFTA) Agreement and the projected rise in FDI in SSA from 2022.
Keywords: 330; FDI; ICT Access; ICT Diffusion; ICT Skills; ICT Usage; Inclusive Growth; sub-Saharan Africa